Preparation Methods of Nanoparticles: A Review of Techniques and Challenges - Jagadish Lakamalla; Sanagarapu Nageswarrao; M. Chinna Eswaraiah (Pharmaceutical Research: Recent Advances and Trends Vol. 10, 2024)
Nanoparticles represent a transformative advancement in drug delivery systems, offering precise targeting, sustained release, and high therapeutic efficacy. This paper explores the various methodologies for producing polymeric nanoparticles, including solvent evaporation, emulsification, nanoprecipitation, and coacervation, each with distinct benefits and limitations in encapsulating diverse drug types. Additionally, it examines the factors influencing nanoparticle properties, such as particle size and surface characteristics, which impact drug release rates and biodistribution. Through an analysis of these techniques, the paper outlines how specific preparation methods can optimize drug solubility and bioavailability, particularly for poorly soluble drugs.